Gedaref watershed soil sampling. - Strohmeier; Stefan (2017)
The soil sampling draft briefly describes Gedaref watershed (terrain), the suggested sample locations, soil sampling depths, and the according sampling techniques (disturbed and undisturbed). Lab analysis will be discussed/suggested separately after clarifying lab analysis options.